Hepatitis E seroprevalence and risk factors in humans and pig in Ghana - Bagulo, H.; Majekodunmi, A.O.; Welburn, S.C.; Bimi, L. (My University, 2022)
Background: Although Hepatitis E virus (HEV) infection has significant negative impact on the health and wellbeing of underprivileged populations, the burden of HEV in Ghana is still unclear, despite widespread water, sanitation, and hygiene (WASH) related conditions that predispose people to the risk of infection. Methods: A cross-sectional study was conducted to explore rates of HEV seroprevalence and HEV prevalence, as well as risk factors in humans and domestic pigs in Ghana. These were determined using ELISAs manufactured by Wantai Beijing Biopharmaceuticals, China. The study involved 1365 community members, 105 pig farmers and 474 domestic pigs from four administrative regions of Ghana. Results: Results showed overall seroprevalence and prevalence of 12.4% and 0.7% in community members and 15.2% and 2.9% in pig farmers respectively. There was no significant difference in the seroprevalence between the two groups (Z = 0.851; p = 0.3953). However, the prevalence in pig farmers was significantly higher than in community members (Z = 2.412; p = 0.016). Age (OR = 1.369, CI = 1.243 – 1.508; p = 0.0000), gender (OR = 1.419, CI = 1.101 – 1.991; p = 0.043), and the region of residence (OR = 1.569, CI = 1.348 – 1.827; p = 0.0000) were significant risk factors for HEV seroprevalence in a multivariate regression model. In pigs, overall seroprevalence and prevalence of 62.4% and 5.5% were recorded respectively. A significant difference in seroprevalence was found between confined (6.7%) and free-range pigs (88.3%), (Z = 7.492; p < 0.00001) in the Volta Region. Multivariate logistic regression showed a significant association between seroprevalence and husbandry (OR = 7.051, CI = 3.558– 13.972; p = 0.0000) and region (OR = 4.602, CI = 2.300 – 9.205; p = 0.0000) in pigs in the Volta and Greater Accra Region. Conclusion: From this study, HEV is endemic in Ghana with high seroprevalence in humans and pig populations. This underscores the need for awareness creation and action for prevention and control.
Research Article
Keywords: Hepatitis E; Pigs; Water; Sanitation; Hygiene